Identidade, cultura e música em Brasília - Guilherme Paiva Carvalho (Ciências Sociais Unisinos)
This research analyzes the relation between identity and music in Brasília in the late 1990s, emphasizing the independent market. In the 1980s, Brasilia became known as the national capital of rock. However, since the foundation of the city other musical styles were also prominent, such as choro, samba, northeastern forró and reggae. Our study emphasizes the cultural musical diversity existing in the city and relates the musical identity in Brasília with the concept of multiculturalism.